Subsidios a la producción y efectos derivados de la formación de una unión aduanera - Méndez, José; Méndez, Luciano (Estudios de Economía, 2016)
Using a three-country reciprocal dumping model, this paper analyses the effectsof tariff unions on welfare taking the possibility of production subsidies intoaccount. Production subsidies are found to prevent the deviation of trade. Resultsare also obtained suggesting that although universal free trade is the mostefficient situation it is not an equilibrium situation, and that regionalliberalization will therefore not lead to universal free trade.